PENGARUH JOIN ORDERING TERHADAP WAKTU RESPON QUERY - Meyliani Tanjung; Wasino Wasino; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The process of retrievingdata in a database is often done in an organization.  In the process, sometimes we need a join query between one relation to another relation. The process of setting up of a join query is very difficult and confusing therefore, this study will present the effect of join ordering and the most optimal way to do join ordering.The study was conductedon AdventureWorksLT Databasee (v2008) Samples RTM (x86)  that has been given additional data using RedGate software. Comparison of the response time is measured through a join query. The results show that the best way to perform a join order is, by joining the large data with the small data first.